(untitled) (Boca Raton, 2014)
This is the first book about fermented food and beverage to focus on solid-state fermentation. The text describes the various reactors used in solid-state fermentation, including static state reactors, dynamic reactors, and other new types of reactors, and provides a detailed introduction to various solid-state fermented foods and beverages, including product category, characteristics, functionalities, safety issues and consumer perception. The authors address such engineering issues as mass and heat transfer and energy equation calculation of solid-state fermentation, dynamic modeling of solid-state fermentation, and process control of solid-state fermentation.
Keywords: Solid-state fermentation.,Lên men trạng thái rắn